Australian Kinship - (USA), Lyle B. Steadman (Гласник Етнографског института САНУ, 2005)
There is a strange custom in Australia, among the Aborigines. A man and his wife give their five-year-old daughter to a young boy to be the little boy’s future mother-in-law. From that moment on, throughout their lives, the boy will call the girl “mother-in-law”, will show her extreme respect, will never be familiar with her, and will send her gifts of meat when he’s successful in hunting. Thirty or forty years later, when they have grown up, the boy’s “mother-in-law” will begin sending him her daughters as wives as they reach fifteen years of age or so. In my talk today I shall use Darwinian selection theory to offer an explanation of this strange custom, which may, until recently, have been extremely widespread, perhaps universal1 in the 500 or so tribes that covered Australia. Key words: Australia, Aborigines, kinship, sections, subsections.